Interpreting Musical Gestures, Topics, and Tropes : Mozart, Beethoven, Schubert - Hatten, Robert S. (Musical meaning and interpretation., 2004)
"This book continues to develop Hatten's theory of musical physical based on the principles of semiotic theory as introduced in Musical Meaning in Beethoven (1994). In Part One, Hatten applies his theories of markedness, topics, and tropes to individual works by Beethoven and Schubert, ending the section with a chapter that presents an overview of topics, genres, and forms as tropes in Baroque, Classical, and Romantic music."